Muscle hypertrophy: A narrative review on training principles for increasing muscle mass - Howe, L. P.; Read, P.; Waldron, M. (Strength and Conditioning Journal, 2017)
Developing muscle cross-sectional area has the potential to enhance performance for many athletes. Because emerging evidence challenges traditional beliefs regarding the prescription of hypertrophy-focused training programs, this review provides an overview of the current literature relating, specifically, to programming variables. Evidence-based recommendations are provided for the design of effective resistance-training programs, with the goal of increasing an athlete's skeletal muscle mass.